Psychopath Behaviour In The Orphan Film By Jaume Collect Serra - ulfa arimawati; alfian alfian; tira mariana (English Literature Department, Adab and Humanities Faculty, 2020)
This film discusses about Psychopath Behaviour in The Orphan Film by Jaume Collet Serra. Pyschopaths are social predators who lure, manipulate, and shattered hopes. This research aims to determaine the behaviour, types and the effects of psychopath in everyday life. The research data are taken from The Orphan film and the script. The data are clarified by using psychopathy theory. The writer uses two theories to answer the formulation of the problem, the first is Stefan’s H. verstappen theory, the second is Robert’s Hare theory. This research uses qualitative descriptive method. Research findings show that first, there are four common types of psychopath; the victim, the artists, malevolent psychopath, professional psychopath, and malevolent is mostly dominant. The second, there are six psychopath behaviour; lack empathy, lack of remorse, irresponsibillity, implusive behaviour, complusive lying, and manipulative, and manipulative is mostly dominant. The last, the effects of main character psychopath behaviour; no regret after killing and uncontrolled emotion.